2022
DOI: 10.3390/s23010062
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning in Diverse Intelligent Sensor Based Systems

Abstract: Deep learning has become a predominant method for solving data analysis problems in virtually all fields of science and engineering. The increasing complexity and the large volume of data collected by diverse sensor systems have spurred the development of deep learning methods and have fundamentally transformed the way the data are acquired, processed, analyzed, and interpreted. With the rapid development of deep learning technology and its ever-increasing range of successful applications across diverse sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 594 publications
(657 reference statements)
0
2
0
Order By: Relevance
“…A large database including more than 31,000 HTDL and URL characteristics was tested, and the results showed that accuracy was 97.24%, True Positive (TP) rate was 4.99%, and False Negative (FN) rate was 2.74% [17]. Author in [18] recommended an intelligent phishing detection method based on website text features to combat zero-day phishing tactics.…”
Section: Related Workmentioning
confidence: 99%
“…A large database including more than 31,000 HTDL and URL characteristics was tested, and the results showed that accuracy was 97.24%, True Positive (TP) rate was 4.99%, and False Negative (FN) rate was 2.74% [17]. Author in [18] recommended an intelligent phishing detection method based on website text features to combat zero-day phishing tactics.…”
Section: Related Workmentioning
confidence: 99%
“…Unlike traditional machine learning algorithms that require manual feature selection and classifier choice, deep learning algorithms automatically extract features through self-learning from errors. This automatic feature extraction sets deep learning apart from the broader field of machine learning [1,92,93]. To train and evaluate a deep CNN model, each input image undergoes a sequence of convolution layers with filters, followed by flattening, pooling layers and fully connected layers.…”
Section: Learning Algorithmmentioning
confidence: 99%
“…The initial ones will trigger a human detector and examine body joints in boundary boxes that have already been determined. Top-down methods include the ones described in PoseNET [25], HourglassNet [26], and Hornet [27]. There are a few other bottom-up methods, such as Open space [28] and PifPaf [29].…”
Section: A Proposed Approachmentioning
confidence: 99%